2007
DOI: 10.1155/2007/65873
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mechanism is Involved in the Gastroprotective Effects of Ozonized Sunflower Oil in Ethanol-Induced Ulcers in Rats

Abstract: This research was performed in order to determine the potential protective effects of ozonized sunflower oil (OSO) in the injury of rat gastric mucosa induced by absolute ethanol and as well as to elucidate the role of reactive oxygen species (ROS), lipid peroxidation, and some important constituents of antioxidant defense such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT) in these effects. OSO was administered to rats intragastrically by a cannula and it was applied during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
(20 reference statements)
2
26
0
3
Order By: Relevance
“…CAT activity was slightly higher in the AaEE + DSS group than in the DSS group, although the difference was not significant; it has been reported that there is an increase in CAT activity by administering natural products as treatments against UC and this appears to be due to the fact that CAT has a lower affinity for that ROS comparing to SOD and GPx. This result comes in concordance with many previous studies that reported that GPx plays a much greater role in the removal of H 2 O 2 than CAT [2931]. Therefore, our findings indicate that AaEE treatment of colitis might be reducing the extent of colonic injury by its antioxidant ability.…”
Section: Discussionsupporting
confidence: 93%
“…CAT activity was slightly higher in the AaEE + DSS group than in the DSS group, although the difference was not significant; it has been reported that there is an increase in CAT activity by administering natural products as treatments against UC and this appears to be due to the fact that CAT has a lower affinity for that ROS comparing to SOD and GPx. This result comes in concordance with many previous studies that reported that GPx plays a much greater role in the removal of H 2 O 2 than CAT [2931]. Therefore, our findings indicate that AaEE treatment of colitis might be reducing the extent of colonic injury by its antioxidant ability.…”
Section: Discussionsupporting
confidence: 93%
“…These processes detoxify endogenous toxic materials such as peroxidized lipids. GPx is an enzyme with peroxidase activity, which reduces lipid hydroperoxides and free hydrogen peroxide to water [26]. GR is an important antioxidant enzyme that reduces glutathione disulfide to the sulfhydryl form of GSH [32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is consensus that the deleterious effects of ethanol on gastric mucosa are consequence of the enhanced lipid peroxidation and decreased glutathione levels [37]. On the other hand, in ischemia-reperfusion model, the injuries occur without the use of chemical agents [38].…”
Section: Discussionmentioning
confidence: 99%